Village voices, forest choices : joint forest management in India - Poffenberger,mark(Editor) Mcgean,Betsy(Editor) (Oxford University Press, 1996)
Village Voices, Forest Choices offers the first comprehensive examination of revolutionary changes occurring in the management of India's forests. Over the past two decades, responding to scarcities, thousands of villages have taken charge of public forests, thereby controlling grazing and cutting. The result has been a striking renewal of once badly degraded ecosystems.